2017
DOI: 10.3920/cep160026
|View full text |Cite
|
Sign up to set email alerts
|

Riders’ perception of symmetrical pressure on their ischial tuberosities and rein contact tension whilst sitting on a static object

Abstract: The horse-rider system is of great interest in understanding the mechanics involved in optimising locomotor function and performance in the ridden horse. Adult riders (n=30) attending a rider conference volunteered to take part in the study. Riders were asked to mimic riding position by positioning themselves symmetrically on their seat bones (ischial tuberosities) sitting on a (Pliance) pressure mat which was placed on a static platform. Riders were also asked to mimic even rein contact using reins with gauge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…This asymmetry will undoubtedly effect the rider's ability to control and communicate with the horse. A balanced rider with aligned posture will be easier for the horse to support (De Cocq et al, 2009;Pelham et al, 2010;Clayton et al, 2017;Guire et al, 2017) whereas a rider that is asymmetric will find it difficult to apply and release appropriate aids (Alexander et al, 2014). This may lead to the horse becoming confused regarding the task and may display adverse behaviours that are associated equine welfare issues (McGreevy and McLean, 2007;Goodwin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This asymmetry will undoubtedly effect the rider's ability to control and communicate with the horse. A balanced rider with aligned posture will be easier for the horse to support (De Cocq et al, 2009;Pelham et al, 2010;Clayton et al, 2017;Guire et al, 2017) whereas a rider that is asymmetric will find it difficult to apply and release appropriate aids (Alexander et al, 2014). This may lead to the horse becoming confused regarding the task and may display adverse behaviours that are associated equine welfare issues (McGreevy and McLean, 2007;Goodwin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship requires clear communication that is reliant on the rider maintaining balance and posture in order to be able to administer predictable cues (aids). The rider aims to maintain a straight line through the ear-shoulder-hip-heel, with the pelvis in the neutral position and a controlled upright trunk position adapting to the movement of the horse (Guire et al, 2017;Hobbs et al, 2014;Nevison et al, 2013;Douglas et al, 2012;Lovett et al, 2005). If the rider is unable to maintain this desirable position then they are less likely to be able to control their body movements, administer repeatable predictable cues to the horse and are increased risk of losing their balance or causing undesirable behaviours in the horse.…”
Section: Introductionmentioning
confidence: 99%
“…A simple study demonstrated that riders have poor awareness of asymmetry when they are sitting on a static object [12]. Furthermore, there is an association between asymmetrical foot pronation and pelvis level in riders when walking and sitting without foot contact [13,14].…”
Section: The Ridden Horsementioning
confidence: 99%
“…It would be useful to be able to predict whether a rider will sit symmetrically with equal weight on both seat bones. When riders sat on a pressure mat on a flat surface and were instructed to weight their seat bones equally, there was significantly higher mean pressure on the left side (3.22 vs. 2.65 N/cm 2 , p = 0.04) [ 12 ] indicating a poor ability to equalize pressure in a static situation, albeit in a different position than during riding. Further investigations are warranted to study relationships between rider balance, posture and weight distribution on the ground and on the horse.…”
Section: Introductionmentioning
confidence: 99%